O etyce zawodowej maklera „towarowego” w świetle prawa giełdowego II Rzeczypospolitej Polskiej i pierwszych lat po II wojnie światowej (do 1950 roku) - Marks, Bogusław Piotr (Annales. Etyka w Życiu Gospodarczym, 2012)
The commodity exchange is regarded as one of the key institutions of market economy. Stockbrokers were a truly essential group of workers of the commodity exchanges. It was on the level of their organization and professional ethics that depended the level of efficient functioning of this institution. The basic law regulations, orders and stock charters were traced in this paper, which marked principles of stockbrokers’ activity. These principles were considered from the point of view of the ethical norms establishing the contemporary ethics of economic life. My special attention was concentrated on these principles of stockbrokers’ activities which concern the way of their appointing, rights as well as duties. „Ethical aspects” of stockbrokers’ activity on the Polish commodity exchanges were traced for the period from 1921 to the 1950. In initial period of the second Republic of Poland acted six commodities exchanges. In 1948 year stockbrokers institution was done away. The comparatively quick unification of exchange law by the government of independent Poland was the expression of understanding the importance which was fulfilled in economy by the institution of commodity exchange. In turn, issuing separate regulations for stockbrokers was proof of high position held by this group in the structure of the basic organs of a commodity exchange.